A storm of infinite beauty : a novel - MacLean, Julianne (Lake Union Publishing, 2023)
Gwen Hollingsworth is the curator at a museum in Nova Scotia dedicated to the Hollywood legend Scarlett Fontaine's life. Gwen is also sole descendant and heir to Scarlett's fortune. Gwen is dealing with a messy marital separation and is struggling to move forward. So when Peter Miller, a biographer and photojournalist, come to the museum with shocking claims about Scarlett, which include a life of exile in Alaska and a baby born in secret, Gwen's whole world is turned upside down. Gwen and Peter set out for Alaska together to uncover the truth, but they soon find themselves on a path toward something far deeper and meaningful than either of them ever expected.